Complex evolution of folds and cleavages in Archean rocks, Yellowknife, N.W.T. - Fyson, W. K. (Canadian Journal of Earth Sciences, 1982)
Overturned folds and later cleavages in a metasedimentary terrain with marginal volcanics near Yellowknife form a complex succession in which structures repeatedly trend eastward and northward. Early major east–west folds are overturned away from a southern granodioritic complex and terminate westward against a major syncline, with limbs overturned inward, trending north–south along the western granitoid boundary of the terrain. Later smaller folds (limbs ~1 km), which die out away from granitoid plutons, include a progression from northerly to easterly trending structures. Several sets of cleavage foliations, mostly steeply inclined, transgress the folds: an east–west set, succeeded by a regionally dominant set striking northwest to north, and a later north–south set confined to near the western margin of the terrain.The easterly and northerly, near-orthogonal trends followed by successive structures could reflect the influence of fault-bounded crustal blocks. During emplacement of fault-controlled granitoid bodies, the blocks may have tilted successively about easterly or northerly axes with gravitational collapse, folding, and overturning of the supracrustal rocks. Further tilting could in part have led to the compressions that formed the cleavages.